Multiple-Use Landscapes: Reclaimed Phosphate Mined Lands - M. Wilson; Edward A. Hanlon (EDIS, 2012)
Phosphate mining is a temporary land use. The jobs and economic activity associated with mining depart an area once the resource is exhausted — but the landscape created as a result of mining and reclamation will exist in perpetuity. Communities affected by mining activities need to have reclamation result in lands with high potential to provide sustainable economic opportunities while maintaining ecosystem services and ecological functions. This 8-page fact sheet provides a brief overview of the landscapes being created as a result of phosphate mining and reclamation activities in Florida. Written by M. Wilson and E.A. Hanlon, and published by the UF Department of Soil and Water Science, October 2012.